Effects of N and O groups for oxygen reduction reaction on one- and two-dimensional carbonaceous materials. (1st June 2020) - Cardoso, Eduardo S.F.; Fortunato, Guilherme V.; Palm, Iris; Kibena-Põldsepp, Elo; Greco, Anderson S.; Júnior, Jorge L.R.; Kikas, Arvo; Merisalu, Maido; Kisand, Vambola; Sammelselg, Väino; Tammeveski, Kaido; Maia, Gilberto
Abstract: Oxygen reduction reaction (ORR) is greatly affected by the morphology as well as the elemental composition of the nitrogen-doped carbon-based electrocatalysts. Thus, this work focuses on: (i) nitrogen doping of different graphene-based materials (two-dimensional materials: chemically converted graphene, graphene oxide, and commercially available graphene, and one-dimensional material: graphene nanoribbons) that differ from each other by morphology as well as elemental composition and (ii) studying the ORR performance of these N-doped carbonaceous catalysts in alkaline medium. The nitrogen doping is achieved by low-cost synthetic method based on hydrothermal treatment at mild conditions. The results indicate that: (i) nitrogen doping is dependent on the carbonaceous substrate used and (ii) these N-doped graphene-based catalysts vary drastically by the electrocatalytic activity for ORR as well as the selectivity for HO2 − and OH − production in alkaline medium. Roughly, predominantly HO 2 − was produced on two-dimensional graphene-based catalysts enriched with low nitrogen content (0.9–1.4 at.%) and mostly OH − was formed on graphene nanoribbons as one-dimensional catalyst containing low amount of nitrogen (2.1 at.%). This work is valuable for giving further insights into the ORR performance on N-doped graphene-based nanocarbons. Graphical abstract: Image 1 Highlights: Nitrogen doping of 1-D and 2-D nanocarbons was achieved by hydrothermal treatment. The N-doping and ORR activity is dependent on the carbonaceous substrate used. 2-D graphene-based catalysts with low nitrogen content produce predominantly HO 2 − . One-dimensional graphene-based catalyst with low nitrogen content produces mainly OH − .